Innovative Technologies of English Learning (Journal of Pedagogical Inventions and Practices, 2022)
The article analyzes the ways to develop students' linguistic, sociolinguistic, pragmatic and strategic competencies in the teaching of English with the help of innovative technologies within the communicative approach, the methodological support for the use of innovative technologies based on the development of independent learning. Keywords: English, innovation, technology, educational technology, interactive, method